Parliamentary and Local Elections in Serbia 2023 - Pavlović, Dušan (Contemporary Southeastern Europe)
The December 2023 Serbian parliamentary and local elections unfolded against the tragicbackdrop of two mass shootings in May, triggering a public outcry and widespreadprotests that demanded increased security measures. Serbia’s political landscape,characterized by a democratic façade but inherently unfair conditions for inter-partycompetition, defined the elections’ outcome. The ruling Serbian Progressive Party (SNS),led by President Vučić, was drawing on its incumbent advantage to realize itspredominance in media representation, misuse public funds, and manipulate voterregisters. The SNS secured an absolute majority with 46% of the votes. However,allegations of electoral irregularities marred the elections. Instead of resolving societalconflicts, the elections deepened existing tensions. Addressing these allegationstransparently and accountably will be crucial for restoring confidence and fosteringpolitical stability in Serbia.